1994
DOI: 10.1002/art.1780370314
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor β1 Regulates Tissue Inhibitor of Metalloproteinases—1 Expression in Differentiated Human Articular Chondrocytes

Abstract: Objective. To investigate the role of interleukin-6 (IL-6) and transforming growth factor pl (TGFp1) in the regulation of tissue inhibitor of metalloproteinases-1 (TIMP-1) synthesis in human articular chondrocytes.Methods. Articular cartilage was obtained from human knee joints 24 hours after death. Chondrocytes were isolated by collagenase digestion and embedded in low-gellingtemperature agarose. After stimulation by cytokines, total RNA was isolated and analyzed by Northern blotting. TIMP-1 protein levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
46
0
4

Year Published

1996
1996
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 53 publications
(26 reference statements)
3
46
0
4
Order By: Relevance
“…It is currently believed that TGFP has a profound stimulatory effect on TIMP-1 production (21). These findings were also confirmed in the present study, which showed the same magnitude as that of OSM.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It is currently believed that TGFP has a profound stimulatory effect on TIMP-1 production (21). These findings were also confirmed in the present study, which showed the same magnitude as that of OSM.…”
Section: Discussionsupporting
confidence: 91%
“…The use of the identical signal-transducing molecule, gp130, which has been reported to be expressed on human chondrocytes (21), suggests that the biologic effects of these cytokines on the metabolism of the connective tissue cells are qualitatively similar. Since IL-6 family cytokines have been reported to stimulate TIMP-1 synthesis in fibroblasts (26), we investigated whether these findings are also confirmed in chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others (14,15,36) showed that TGF-␤ can increase PTG synthesis in normal and OA chondrocytes in vivo and in vitro. Furthermore, local administration of TGF-␤ can suppress IL-1-induced matrix degradation (17,37), probably via down-regulating MMPs (38, 39) and/or increasing the level of TIMPs (38,40). TGF-␤ also inhibits terminal differentiation of chondrocytes (hypertrophy), which has been shown to occur during OA.…”
Section: Discussionmentioning
confidence: 99%